The relationship between self-control and learning engagement among Chinese college students: the chain mediating roles of resilience and positive emotions - Yang, Yue-Di; Zhou, Chi-Liang; Wang, Zi-Qing (Frontiers in psychology, 2024)
As the main driver of talent cultivation in colleges and universities, the learning and development level of college students is a core indicator of the quality of talent cultivation. The current status of college students' learning has always been a heavily researched topic. However, there is a lack of academic research on the potential mechanisms of self-control about how it affects college students' learning engagement. This study explored the relationship between college students' self-control and learning engagement and the potential mechanisms underlying this relationship with reference to a large sample. A total of 765 college students from Guangxi, China, completed the self-control scale, the resilience scale, the positive emotions scale, and the learning engagement scale. SPSS 26.0 was used to conduct common method bias tests, descriptive statistics, correlation tests, and regression analyses. Structural equation modeling was constructed using AMOS 26.0, and mediation effects were tested. This article mainly used questionnaires to collect data and, on this basis, examined the relationship between self-control, resilience, positive emotions, and the learning engagement of college students. The results showed that (1) self-control positively affected college students' learning engagement; (2) resilience partially mediated the relationship between self-control and college students' learning engagement; (3) positive emotions partially mediated the relationship between self-control and college students' learning engagement; and (4) resilience and positive emotions played a chain-mediating role between self-control and college students' learning engagement. The present study identifies the potential mechanism underlying the association between the self-control and learning engagement of college students. The results of this study have practical implications for enhancing the learning engagement of Chinese college students by increasing their psychological resources and improving the teaching of university teachers.